Kepribadian Tahan Banting Kader Kesehatan Jiwa Masyarakat Dalam Mendampingi ODGJ - Ramahwati; Muslimah Zahro Romas; Syariful (Universitas Darul Ulum, 2026)
The increasing prevalence of mental health disorders in urban areas highlights the vital role of community mental health workers in assisting individuals with mental illness. This study aims to describe the hardiness personality of community mental health workers in the Kemantren Kraton area. A qualitative phenomenological approach was used with three participants selected through saturation sampling. Data were collected through semi-structured interviews, participatory observation, and documentation, then analyzed using the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing. The findings show that hardiness is reflected in three main aspects: commitment, control, and challenge. Commitment appears in the workers’ active engagement in meaningful social and professional activities. Control is reflected in their ability to manage complex situations with confidence and a sense of responsibility. Challenge is demonstrated through the ability to interpret difficulties as opportunities for growth and social contribution. The study concludes that hardiness serves as a key psychological resource that enables community mental health workers to maintain emotional balance, cope effectively with stress, and sustain motivation in community-based mental health services.